Peningkatan Kompetensi Guru dalam Pengajaran STEAM untuk Mendukung Proyek P5 di Sekolah Kabupaten Gowa - Nur Aisyah Ainun; Ismail, Ismail; Bahri, Arsad; Patongai, Dian Dwi Putri Ulan Sari; GH, Muliana; Isrul, Muhammad (Program Studi Manajemen FEB UNM, 2025)
STEAM-based learning in Gowa district has not been optimised despite its relevant local potential. Teachers have difficulty integrating science, technology, art, engineering and mathematics into the P5 Project. Community service activities are designed with the aim of improving teacher competence through practice-based training, intensive mentoring, and the formation of learning communities. This programme also aims to strengthen the implementation of Merdeka Curriculum, which emphasises collaborative and contextual learning. Participants totalled 20 high school teachers from various schools. The initial stage of socialisation showed the urgency of training, because 75% of teachers had never developed a STEAM-based project. The workshop then produced a simple hydroponic project design. Quantitative data showed an increase in concept understanding from 45% to 82% and project design skills from 42% to 80%. The satisfaction survey recorded that 90% of teachers considered the activities relevant to their needs. The satisfaction survey recorded 90% of teachers rated the activities as relevant to their needs. Qualitative data shows that teachers feel more confident in integrating across disciplines, students show high engagement during project implementation, STEAM learning communities begin to form as a means of sustainability. This fact confirms that the combination of socialisation, training and mentoring is able to address teachers' needs. A brief conclusion states that the programme has succeeded in significantly improving teacher competence. This effort strengthens the implementation of Merdeka Curriculum, confirms the urgency of practice-based training, while supporting the achievement of P5 Project objectives in Gowa District schools.